HAKIKAT BUDAYA JAWA KAITANNYA DENGAN AGAMA HINDU DI BALI - Poniman (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
The existence of Balinese culture has taken place in the presence of foreign influences. Similarly, when Hinduism and Buddhism were embraced by Balinese people. It also affects Hinduism in Bali, which until now seems dominant and gives a hue and coloring the culture and life of Balinese people. Until now, the existence of the Religion and Culture of Bali faced global challenges, the challenges of materialism, and even the impact of the development of Social Media influenced Balinese culture. Knowing the Nature of Javanese Culture in relation to the development of Hinduism in Bali forms the character of Balinese Hinduism which eventually becomes the Balinese Culture. Hinduism in Bali is more visible in Adat and Tradition, this is due to the formation of Religion as a real-life practice. So that the existence of Hinduism is not clearly seen with the Wedanya book as the guiding basis but Lontar-Lontar which is used as a practice in adat both in rituals and literature so it is not found when religious events use Vedas as reading material in Pura and in ritual guidelines.